2017
DOI: 10.1080/14767058.2017.1402881
|View full text |Cite
|
Sign up to set email alerts
|

Initial neonatal resuscitation: skill retention after the implementation of the novel 24/7 HybridLab® learning system

Abstract: As a result of the application of the HybridLab training technique, practical skill retention among medical students after 6 and 12 months dropped by only about 13%. A recall system significantly improved practical skill retention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 18 publications
0
12
0
2
Order By: Relevance
“…There are papers adapting NRP to undergraduates, but the challenge is still to gauge its effectiveness. [22][23][24][25] We showed that it is simple to use basic principles of education theory in planning such activity for undergraduates. Further studies should be conducted by following graduates having applied such experience.…”
Section: Discussionmentioning
confidence: 95%
“…There are papers adapting NRP to undergraduates, but the challenge is still to gauge its effectiveness. [22][23][24][25] We showed that it is simple to use basic principles of education theory in planning such activity for undergraduates. Further studies should be conducted by following graduates having applied such experience.…”
Section: Discussionmentioning
confidence: 95%
“…Their ANTS performance remained higher than that of the control group. The role of debriefing on retention of learning was already underlined in some studies [ 25 , 38 ]. Few studies assessed the retention of learning after screen-based simulation training.…”
Section: Discussionmentioning
confidence: 99%
“…Retention of learning has been studied extensively after different simulation training in health sciences [ 23 ] and neonatal resuscitation [ 2 , 24 , 25 ]. However, the mean retention time of learning after simulation training and the optimal time interval between two formations remain debated [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Existen varios trabajos que adaptaron el PRN a los estudiantes universitarios, pero el desafío sigue siendo estimar su eficacia. [22][23][24][25] Hemos demostrado que es sencillo aplicar los principios básicos de las teorías de la educación para planificar este tipo de actividad destinada a los estudiantes universitarios. Se requieren estudios futuros con un seguimiento de los graduados que aprovecharon esta experiencia.…”
Section: Conclusionesunclassified